The Phenomenon of Dissemination Da'wah Using New Media During the Lockdown Era in Indonesia - Rolando, Dede Mercy; Koroglu, Osman; Putra, Robby Aditya (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
This study focuses on the adaptation of preacher to new media technologies during the Covid-19 pandemic. To examine this phenomenon, the writer uses a descriptive qualitative approach with the type of library research. The results of this study show that the Covid-19 pandemic in Indonesia has made the level of internet use increasing and massive. Of course, this gives a new change and color for the continuity of da'wah. Previously, preacher were more dominant in using the pulpit or gathering mass in one place when carrying out da'wah activities. But not in the current situation. Preacher are required to be adaptive to new media technology. The use of YouTube social media during the Covid-19 pandemic has become an option for preacher to maintain and deliver da'wah messages. Because YouTube is the social media with the top ranking in 2021. In addition, the significance of the use of YouTube social media is seen through its characteristics which are network, interactive, interface, informative, interactive and can also be real-time.